Heidegger at the Gates of Dialectical Materialism. What’s Left of (New Media) Technology? - Peović Vuković, Katarina (Stasis, 2016)
There are two theoretical anchors of this endeavor: the ontological perspective and the dialecticalmaterialist perspective. While dialectical materialism stresses the role of antagonism created by technological progress, the ontology of technology brings research to the question of essence, or specific technological (en)framing. This paper will try to prove that both the ontological and the dialecticalmaterialist perspective are substantial in the research of technology. Contemporary theory of new media rarely includes both theoretical principles, moreover the two perspectives are usually thought to be unrelated.